Higher, Medium and Lower Order Thinking Skills in the Book Al-‘arabiyah Baina Yadaik - Nur Fadilah Amin; Nasruni Nasruni; Nurkhamimi Zainuddin; Azzahratul Mutmainnah (Institut Agama Islam Negeri Curup, 2024)
Arabiyatuna: Jurnal Bahasa Arab Vol. 7. No. 2, November 2023 (page: 795-816)